(untitled) (International Journal of Innovative Technologies in Economy, 2025)
This article discusses the importance of strengthening marketing strategies for Micro, Small, and Medium Enterprises (MSMEs) in rural areas, particularly through an integrated training approach that focuses on improving understanding of basic marketing concepts. In villages, MSMEs still rely on traditional marketing methods that are limited to social networks and the local environment, making it a major challenge to expand their markets to a larger scale. The lack of technology utilization, inadequate education, and limited access to information are the main barriers for MSMEs in adopting more effective modern marketing strategies. To date, the marketing theories discussed include understanding the concepts of needs, wants, and demand. The importance of market segmentation and the marketing mix are 4P (Product, Price, Place, Promotion) and 3P (People, Process, Physical Evidence). The application of these theories also emphasizes that MSMEs need to understand local consumer behaviour, build a strong brand identity, and leverage social media and digital platforms to expand their market reach. Through structured training involving collaboration between universities and communities, it hoped that MSMEs can improve their institutional performance, strengthen customer relationships, and sustainably contribute to overall local economic growth.